Answer: Third option
![-u-v = <-2, -3>](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fw7rfpswp9cjx1vbs6430trhrs2486w5j1.png)
Explanation:
We have the vector u and the vector v. We must perform the operation
.
To perform this operation multiply the vector u by -1 and multiply the vector v by -1.
If u = (-5,6)
So
-1u = (5, -6)
If v = (7, -3)
So
-1v = (-7, 3)
Then the sum of both vectors is done by adding the components of u with the components of v.
![-u-v = (5, -6) + (-7,\ 3)\\\\-u-v = (5-7\ ,\ -6 + 3)\\\\-u-v = (-2,\ -3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9rz6wugltouiygurodjut6bjszj2rh8h7q.png)